Teaching the Introductory Public Relations Course: Pedagogical Recommendations - LaKesha N. Anderson (Central States Communication Association, 2019)
This article explores the foundations and the content areas that ground the introductory public relations course. Examples of two assignments designed to help students think critically, apply knowledge, and improve their writing skills are offered, as well as the identification of several challenges both students and instructors face and a brief discussion of the unique advantages provided by this course.